Laquinimod dampens IL-1β signaling and Th17-polarizing capacity of monocytes in patients with MS - Engel, Sinah; Jolivel, Valérie; Kraus, Stefan H.-P.; Zayoud, Morad; Rosenfeld, Karolina; Tumani, Hayrettin; Furlan, Roberto; Kurschus, Florian; Waisman, Ari; Luessi, Felix (Neurology: Neuroimmunology & Neuroinflammation ; official journal of the American Academy of Neurology, 2021)
Objective To assess the impact of laquinimod treatment on monocytes and to investigate the underlying immunomodulatory mechanisms in MS. - Methods In this cross-sectional study, we performed in vivo and in vitro analyses of cluster of differentiation (CD14+) monocytes isolated from healthy donors (n = 15), untreated (n = 13), and laquinimod-treated patients with MS (n = 14). Their frequency and the expression of surface activation markers were assessed by flow cytometry and the viability by calcein staining. Cytokine concentrations in the supernatants of lipopolysaccharide (LPS)-stimulated monocytes were determined by flow cytometry. The messenger ribonucleic acid (mRNA) expression level of genes involved in cytokine expression was measured by quantitative PCR. The LPS-mediated nuclear factor kappa-light-chain-enhancer of activated B-cell (NF-κB) activation was determined by the quantification of the phosphorylation level of the p65 subunit. Laquinimod-treated monocytes were cocultured with CD4+ T cells, and the resulting cytokine production was analyzed by flow cytometry after intracellular cytokine staining. The interleukin (IL)-17A concentration of the supernatant was assessed by ELISA. - Results Laquinimod did not alter the frequency or viability of circulating monocytes, but led to an upregulation of CD86 expression. LPS-stimulated monocytes of laquinimod-treated patients with MS secreted less IL-1β following a downregulation of IL-1β gene expression. Phosphorylation levels of the NF-κB p65 subunit were reduced after laquinimod treatment, indicating a laquinimod-associated inhibition of the NF-κB pathway. T cells primed with laquinimod-treated monocytes differentiated significantly less into IL-17A-producing T helper (Th)-17 cells. - Conclusions Our findings suggest that inhibited NF-κB signaling and downregulation of IL-1β expression in monocytes contributes to the immunomodulatory effects of laquinimod and that the impairment of Th17 polarization might mediate its disease-modifying activity in MS.
First published November 17, 2020
Gesehen am 02.03.2021